2010
DOI: 10.1007/s10552-010-9635-1
|View full text |Cite|
|
Sign up to set email alerts
|

Assessing environmental and occupational risk factors for lung cancer in Mexican–Americans

Abstract: Although we found over a two-fold increased risk of lung cancer among Mexican-Americans for pesticides, we could not identify individual pesticides. Our findings are an important preliminary step in identifying factors that are specifically associated with lung cancer risk among Mexican Americans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…We have previously reported that the CBMN assay is a sensitive and specific predictor of lung cancer risk (34, 35) and we further found an increase in lung cancer risk for participants that self-reported exposure to asbestos, fiberglass, wood dust, solvents, bleach and pesticides(36) (37, 38). Based on these findings we conducted the current study to evaluate the extent of genetic instability (using the CBMN assay) in lung cancer cases and controls exposed to environmental agents (namely asbestos, fiberglass, wood dust, solvents, paints, exhaust, and bleach) and the effect of smoking on modulating such genetic instability.…”
Section: Introductionmentioning
confidence: 54%
“…We have previously reported that the CBMN assay is a sensitive and specific predictor of lung cancer risk (34, 35) and we further found an increase in lung cancer risk for participants that self-reported exposure to asbestos, fiberglass, wood dust, solvents, bleach and pesticides(36) (37, 38). Based on these findings we conducted the current study to evaluate the extent of genetic instability (using the CBMN assay) in lung cancer cases and controls exposed to environmental agents (namely asbestos, fiberglass, wood dust, solvents, paints, exhaust, and bleach) and the effect of smoking on modulating such genetic instability.…”
Section: Introductionmentioning
confidence: 54%
“…30 In our study, household income, another SES measure, was not associated with rates of ever-smoking for Hispanic men. greater exposure to occupational carcinogens among those with lower nSES 34 may also diminish the positive effect of nSES on lung cancer incidence, particularly among Hispanic men. Overall, the positive nSES gradient in NSCLC incidence seen among Hispanic men was based on relatively weaker and mixed associations.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that chloroform (2.9e24.6 mg m À3 ) and carbon tetrachloride (0.25e459 mg m À3 ) concentrations significantly increased during the use of bleach containing products corresponding to during/before concentration ratios of 8e52 (25 AE 14, average AE SD) for chloroform and 1e1170 (146 AE 367, average AE SD) for carbon tetrachloride, respectively (Odabasi, 2008). It was suggested that the bleach use can be important in terms of inhalation/dermal exposure to carbon tetrachloride, chloroform and several other halogenated VOCs (Bondi, 2011;McHugh et al, 2010;Odabasi, 2008). It was also shown that a substantial amount of chloroform is emitted into the indoor air as a result of chlorine bleach use in residential washing machines (Shepherd et al, 1996).…”
Section: Introductionmentioning
confidence: 99%